2019
DOI: 10.1155/2019/2721578
|View full text |Cite
|
Sign up to set email alerts
|

Speed of Retinal Vascularization in Retinopathy of Prematurity: Risk and Protective Factors

Abstract: Objective. The objective was to study the risk and protective factors involved in retinal vascular development of preterm infants with retinopathy of prematurity. Methods. Between 2000 and 2017, 185 preterm infants were included in the protocol for retinopathy of prematurity. Risk factors associated with speed of retinal vascularization <0.5 disc diameter/week were studied in each of them. Results. The statistically significant variables related to retinal vascular development <0.5 DD/w were intubation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For example, reducing the duration of mechanical ventilation affects the model both directly and indirectly by increasing the rate of vascularisation. Moreover, greater postnatal weight gain will produce a faster vascularisation of the retina [38]. Other risk factors, such as the need for blood transfusions or the presence of sepsis, are significant in the univariate analysis but disappear in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, reducing the duration of mechanical ventilation affects the model both directly and indirectly by increasing the rate of vascularisation. Moreover, greater postnatal weight gain will produce a faster vascularisation of the retina [38]. Other risk factors, such as the need for blood transfusions or the presence of sepsis, are significant in the univariate analysis but disappear in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The specific etiology of ROP is unknown, however it is believed to be associated with aberrant blood vessel proliferation in preterm newborns' retinas (32).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort by Larraya et al, 185 preterm infants were studied for speed of retinal vascularization, however, the authors did not address about the need to treatment or treatment effect. They reported that in multivariate analysis, intubation, high grade bronchopulmonary dysplasia, and poor weight gain at 4–6 weeks after birth, were significantly associated with speed of retinal vascularization < 0.5 disc diameter/week [ 13 ]. Hence, understanding an infant overall clinical picture is valuable in estimating the time to full vascularization.…”
Section: Discussionmentioning
confidence: 99%